On the 160th anniversary of Ivan V. Michurin’s birth - N. P. Goncharov; N. I. Savel’ev (Вавиловский журнал генетики и селекции)
October 2015 marks the 160th anniversary of the birth of Ivan V. Michurin. As a scientist and plant breeder, he made a significant improvement of many varieties of fruit, berry, and flowers. He developed methods of plant breeding, promoted gardening to the north and east of Russia, including Siberia. He introduced some new berry species as Actinidia and black chokeberry and was the first in the country who used dwarf and semi dwarf stocks of apples. Michurin initiated the mass movement of fancier gardeners and horticulture experimenters in USSR who changed and significantly extended the species and geographic ranges of fruit and berry cultivation in Russia. He not only made a vast collection of species and varieties of fruit plants from around the world but also organized their involvement and widespread use in the breeding by hybridization, including interspecific crosses. He created some new artificial interspecific hybrids such as Cerapadus (cherry and bird cherry hybrid), and others. Michurin created 132 cultivars. Eleven of them are not only cultivated but also included in the “National Register of Protected Plant breeding Achievements of the Russian Federation”. Michurin, having lived a long productive life, did not come to the time when he was not only declared “the great nature transformer”, but also “appointed” creator of “Michurin’s theory”, so-called “Creative Darwinism”. However, thirty years later, scientists, though rarely, but still tried to separate his name from Lysenkoism and rehabilitate the scientist.